Resistance of Acanthamoeba Cysts to Disinfection Treatments Used in Health Care Settings - Coulon, Céline (American Society for Microbiology (ASM), 2010)
Free-living amoebae that belong to the genus Acanthamoeba are widespread in the environment, including water. They are responsible for human infections and can host pathogenic microorganisms. Under unfavorable conditions, they form cysts with high levels of resistance to disinfection methods, thus potentially representing a threat to public health. In the present study we evaluated the efficacies of various biocides against trophozoites and cysts of several Acanthamoeba strains. We demonstrated that disinfectant efficacy varied depending on the strains tested, with environmental strains demonstrating greater resistance than collection strains. Trophozoites were inactivated by all treatments except those using glutaraldehyde as an active compound: for these treatments, we observed resistance even after 30 min exposure. Cysts resisted many treatments, including certain conditions with glutaraldehyde and other biocides. Moist heat at 55°C was not efficient against cysts, whereas exposure at 65°C was. Several chemical formulations containing peracetic acid, hydrogen peroxide, or ortho-phthalaldehyde presented greater efficacy than glutaraldehyde, as did ethanol and sodium hypochlorite; however, some of these treatments required relatively long incubation times to achieve cyst inactivation. Amoebal cysts can be highly resistant to some high-level disinfectants, which has implications for clinical practice. These results highlight the need to consider the effective disinfection of protozoa in their vegetative and resistant forms due to their intrinsic resistance. This is important not only to prevent the transmission of protozoa themselves but also due to the risks associated with a range of microbial pathogens that are found to be associated intracellularly with these microorganisms.